The Role of Risk Factors in the Early Manifestation of Gout in Young Women: A Case Report - BASHOR, FURQON ABDULLAH; pratiwi, Prasetyaning Estu (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
ABSTRACT Introduction: Gout is an inflammatory form of arthritis caused by the deposition of monosodium urate crystals in tissues and joints due to hyperuricemia. Although it is more common in middle-aged men, the increasing incidence in young women with genetic predisposition and certain lifestyle factors has become a clinical concern. Early identification and management of risk factors are crucial to prevent disease progression. Case Illustration: A 33-year-old woman with a family history of gout and dyslipidaemia presented with intermittent joint pain in the lower extremities exacerbated by consumption of high-purine foods. The patient was diagnosed with hyperuricaemia in 2017 but did not undergo regular follow-up. Use of allopurinol and corticosteroids was effective in alleviating symptoms, but the complaints persisted. Discussion: This case illustrates the significant role of hereditary risk factors, high-purine dietary patterns, and inadequate medical supervision in the onset of early gout. Pathophysiologically, gout begins with chronic hyperuricemia, which then triggers an inflammatory process through uric acid crystallisation. Genetic factors such as the T allele at SNP rs2231142 of the ABCG2 gene are known to impair uric acid excretion through the intestines, increasing the risk of hyperuricemia and early-onset gout. Epidemiological evidence shows a 3.64-fold increased risk of gout in individuals with high genetic risk and unhealthy lifestyles. Conclusion: The manifestation of gout in young women is the result of a complex interaction between genetic predisposition, environmental factors, and lifestyle. Early detection of risk factors and lifestyle-based interventions particularly a low-purine diet and monitoring of uric acid levels are key approaches in the prevention and management of gout in the productive age population.